ANALISIS KESALAHAN EJAAN BAHASA INDONESIA PADA ABSTRAK SKRIPSI MAHASISWA PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR - Himayatu Sofiah; Indra Permana; Yusep Ahmadi (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research article aims to examine Indonesian spelling errors in student thesis abstracts where writing errors are found. Student mistakes in writing thesis abstracts sometimes do not use the correct Indonesian spelling. The method used in this study is a qualitative descriptive method and data collection procedures in the form of observation. Based on the results of the research, the samples taken were 10 thesis abstracts of IKIP Siliwangi Elementary School Teacher Education Studies program. In writing an abstract, there is a language spelling that is not correct according to the Enhanced Indonesian Spelling Guidelines (EYD), namely the use of prepositions, the use of capital letters, writing full stops, the use of italics and errors in writing words. There are 16 spelling errors in the abstract of Elementary School Teacher Education students. Based on the results of the discussion above, it can be concluded that there was an inaccuracy of the author in using language spelling in italics, capital letters, prepositions, writing periods and errors in writing words.